La Lechucita Canela (Aegolius harrisii) en las provincias de Formosa, Chaco y Corrientes, Argentina - Bodrati, Alejandro; Fariña, Néstor; Pearman, Mark; Pagano, Luis G. (Nuestras Aves, 2016)
Este artículo no cuenta con un resumen.